Analisis Kesiapan Kerja Mahasiswa Di Era Revolusi Industri 4.0 Ditinjau Dari Soft Skills Mahasiswa - Moh. Usman Kurniawan (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
This research aims to know how many students are ready and less ready to face the era of the industrial revolution 4.0. Hopefully, the results of this research can provide solutions and recommendations regarding actions that universities should take, especially students, to be better prepared to face the industrial revolution 4.0. The number of samples used was 49 IKIP PGRI Jember students and final-semester students (semester 7 ≥). The data collection method uses a work readiness scale with 20 questions and 5 alternative answers, while data analysis uses data and uses the Rasch model. The results showed that 38 students (78%) had high job readiness, while the rest were classified as moderate. The elements of the student work-readiness scale item (item measure) show that the ability to work in IKIP PGRI Jember student teams is very high, exceeding other items.